Automated Measurement of Sural Nerve Conduction is a Useful Screening Tool for Peripheral Neuropathy in Type 1 Diabetes Mellitus (The Review of Diabetic Studies, 2019)
We examined the diagnostic performance of the portable NC-stat DPNCheckTM device (Neurometrix, Inc., Waltham, MA, USA) for automated measurement of sural nerve conduction in the diagnosis of diabetic peripheral neuropathy (DPN) in subjects with type 1 diabetes mellitus (T1DM). We included 53 consecutive T1DM subjects (28 men) with mean age 36.9 years and mean T1DM duration 14.6 years. Exclusion criteria were B12 depletion, alcohol abuse, and other causes of peripheral neuropathy.